Differences in processing strategies between non-soy legumes and soybean: a review - Liu, Tong; Wang, Mingyu; Shen, Yue; Lyu, Bo (Frontiers in Sustainable Food Systems, 2025)
IntroductionAs consumers continue to demand healthy diets and plant-based foods, the acceptance of bean foods, especially non-soy legumes, is gradually increasing. Since the industrial processing of non-soy legumes has just started, it has borrowed many processing strategies from soybeans. However, since the basic ingredients, processing characteristics, and nutritional properties of non-soy legumes are different from those of soybeans, their processing strategies should also be different.MethodsThis paper systematically reviews and compares the similarities and differences between processing strategies for soybeans and non-soy legumes.ResultsSeveral suggestions are proposed in this paper, which provide a theoretical basis and strategic recommendations for the industrial processing of non-soy legumes.DiscussionSeveral issues have been raised simultaneously, and their proper resolution will contribute to the high-quality development of non-soy legumes processing industry.